A real-time quantitative polymerase chain reaction for the specific detection of Hammondia hammondi and its differentiation from Toxoplasma gondii - Schares, Gereon; Globokar Vrhovec, Majda; Tuschy, Mareen; Joeres, Maike; Bärwald, Andrea; Koudela, Bretislav; Dubey, Jitender P; Maksimov, Pavlo; Conraths, Franz J (Parasites & vectors, 2021)
INTRODUCTION: Hammondia hammondi and Toxoplasma gondii are closely related protozoan parasites, but only T. gondii is zoonotic. Both species use felids as definitive hosts and cannot be differentiated by oocyst morphology. In T. gondii, a 529-base pair (bp) repetitive element (TgREP-529) is of utmost diagnostic importance for polymerase chain reaction (PCR) diagnostic tests. We identified a similar repetitive region in the H. hammondi genome (HhamREP-529). METHODS: Based on reported sequences, primers and probes were selected in silico and optimal primer probe combinations were explored, also by including previously published primers. The analytical sensitivity was tested using serial dilutions of oocyst DNA. For testing analytical specificity, DNA isolated from several related species was used as controls. The newly established TaqMan PCR (Hham-qPCR1) was applied to tissues collected from H. hammondi-infected gamma-interferon gene knockout (GKO) mice at varying time points post-infection. RESULTS: Ten forward and six reverse primers were tested in varying combinations. Four potentially suitable dual-labelled probes were selected. One set based on the primer pair (Hham275F, Hham81R) and the probe (Hham222P) yielded optimal results. In addition to excellent analytic specificity, the assay revealed an analytical sensitivity of genome equivalents of less than one oocyst. Investigation of the tissue distribution in GKO mice revealed the presence of parasite DNA in all examined organs, but to a varying extent, suggesting 100- to 10,000-fold differences in parasitic loads between tissues in the chronic state of infection, 42 days post-infection. DISCUSSION: The use of the 529-bp repeat of H. hammondi is suitable for establishing a quantitative real-time PCR assay, because this repeat probably exists about 200 times in the genome of a single organism, like its counterpart in T. gondii. Although there were enough sequence data available, only a few of the primers predicted in silico revealed sufficient amplification; the identification of a suitable probe was also difficult. This is in accord with our previous observations on considerable variability in the 529-bp repetitive element of H. hammondi. CONCLUSIONS: The H. hammondi real-time PCR represents an important novel diagnostic tool for epidemiological and cell biological studies on H. hammondi and related parasites.
Keywords: Feces; diferenciální diagnóza; Cats; Real-Time Polymerase Chain Reaction; repetitivní sekvence nukleových kyselin; toxoplazmóza zvířat; Hammondia hammondi; molekulární patologie; Toxoplasmosis, Animal; Quantitative polymerase chain reaction; Oocysts; Mice; Sarcocystidae; TaqMan polymerase chain reaction; oocysty; kočky; kvantitativní polymerázová řetězová reakce; Repetitive Sequences, Nucleic Acid; Faecal examination; zvířata; feces; protozoální geny; Toxoplasma; Genes, Protozoan; Coccidiosis; Oocyst; myši; Diagnosis, Differential; kokcidióza; Pathology, Molecular; Animals